Percepção de atores sociais e análise de políticas públicas locais visando a provisão de serviços ecossistêmicos - Fernandes, Jamily da Silva (2021)
Landscape changes have been often characterized by bad land use planning and ecosystem management, highlighting the need for strategies that maintain or restore services and generate benefits for human well-being and environmental quality. This research aimed the evaluation of two interrelated and complementary municipal programs in Louveira, SP: the first (Municipal Fruit Growing Incentive Program - PROMIF), focuses on good practices in land use and strengthening family farming, and the second (Louveira Environmental Services Payment Program - PSAL) focuses on payment for environmental services, linked to forest restoration in areas of public water supply. Thus, we sought to: (i) analyze the relationship of these programs with the agenda of sustainability and ecosystem services, (ii) analyze their relationship with land use in Louveira, (iii) analyze the perception of farmers in relation to forest restoration and its association with ecosystem services, (iv) evaluate the participation and engagement of farmers in the process of implementing both programs, (v) analyze the perception of different social actors about these two public policies and understand their expectations, (vi) identify the main factors that influence their operational environment, limiting or fostering their effectiveness. For this, we collected primary and secondary data, and adopetd a series of different strategies: presence and participation of the research team in meetings and events about the programs, consultations on public documents and dialogues with the municipal secretariats responsible for them, application of questionnaires, focal groups and semi-structured interviews. We found that PROMIF and PSAL are causally related to the sustainability agenda, recognizing the role of rural landscapes in promoting local development and providing for actions aimed at the provision of ecosystem services. Farmers recognize the importance of forests for the provision of these services, especially the protection of water resources. However, their participation has been limited only to the condition of beneficiaries, without involvement in decision-making processes. From a SWOT analysis, two factors were considered by the interviewed actors as threats to the permanency of the programs: dependence on political decisions and financial sources to fund them. The main strengths identified in the statements were the practice of sustainability, through good practices, environmental concern by the farmers, and the payment of subsidies to them. All weaknesses and some threats refer to gaps in farmers' participation and understanding of the programs. It was concluded that decision makers need to seek more alternatives to bring farmers closer to the programs, making them more than mere recipients of the developed actions. Therefore, even with the subsidies granted, farmers still have an impasse to balance environmental issues - through the maintenance or inclusion of the tree and forestry component in the properties - and the economic and productive needs.